The Implementation of Jigsaw to Improve Madrasah Tsanawiyah Students’ Fiqih Achievement - Qurrotul Ainiyah; Ali Mustofa (AL-ISHLAH: Jurnal Pendidikan, 2022)
Learning fiqih needs more time to make students understand and practice it. One of the successes of learning process is learning model. Jigsaw as leaning model causes students actively involved in learning process therefore, it increases their cognitive, affective, and psychomotor ability. This research was aimed to describe the implementation of jigsaw as model and the improvement of students’ fiqih ability at a private Madrasah Tsanawiyah Mojokerto. This study used qualitative descriptive. The data was collected by observation, documentation, and interview.  Data then was analyzed with interactive model, such as collecting, display, condensation, and verification data. The research result were the implementation of the model consisted of five stages, namely identification of problems; representation of problems; implementation of problem solving plans, implementing plans and assessing solution results. The results were the cognitive aspect (knowledge) was increasing students learning achievement in terms of their daily test scores. The affective aspect (attitude) was the student became more enthusiastic in participating the teaching and learning process. Meanwhile, from the psychomotor aspect (skills) was the students became more self-confidence to appear in front of the class. The conclusion is the implementation of jigsaw in fiqih learning is in accordance with theory, and it causes the students are more accomplished.